DINAMIKA PERENCANAAN KEUANGAN IBU RUMAH TANGGA DITINJAU DARI LITERASI, PENDAPATAN, DAN DUKUNGAN PASANGAN - Nuraeni Hadiati Farhani; Dini Ayuning Ratri Sukimin; Asterina Anggraini (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
In times of economic uncertainty, the ability of families to manage their finances becomes increasingly important. In rural areas, where income is often limited and unstable, poor financial planning can lead to serious financial difficulties. This study aims to explore how housewives in a village in Bandung Regency manage household finances, focusing on the role of financial literacy, income level, and husband’s support. Using a descriptive qualitative method with a deductive approach, data were collected through in-depth interviews with ten housewives from both lower- and middle-income households. The results show that most respondents had never received formal financial education. Instead, their financial knowledge came from personal experience and social media. Housewives from low-income families generally focused on short-term budgeting, prioritizing daily needs, while those with more stable incomes practiced monthly planning and saving. Husband’s involvement and support proved to be an important factor influencing a woman’s ability to plan effectively. The study concludes that in the current economic climate, improving financial literacy and encouraging spousal collaboration are essential to strengthening financial planning among rural households. A context-based approach to financial education is needed to help housewives make informed and sustainable financial decisions.